ALS560 : Research methodology / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2021)
This course introduces students to applied language research methods and emphasizes the need to use evidence for informed decision-making. Students will become familiar with the systematic processes needed to ensure the reliability and validity of quantitative, qualitative and mutli method approaches of enquiry. The course emphasizes theoretical and practical issues in research design and methodology. At the end of the course, the students demonstrate their knowledge and skills required for writing a research proposal.